Lingupoetic Analysis of Poems Translated from Uzbek to French - Eshboyeva Tursuntosh (Zien Journals, 2023)
This article examines the linguopoetic characteristics of poems translated from Uzbek to French. The poem "Tavollo" by Muhammad Yusuf, one of the Uzbek poets, was subjected to linguopoetic analysis. Theoretical conclusions are based on the comparative analysis of the texts. The characteristics of poetic translation, the complexity of translation methods with the periodical change and improvement of poetic genres, and the differences between them were analyzed.
Keywords: Artistic translation; poetic translation; image